2018
DOI: 10.4066/biomedicalresearch.29-17-2888
|View full text |Cite
|
Sign up to set email alerts
|

Influences of family-centered maternity care nursing on puerperal depression of delivery women during puerperal period

Abstract: Objective: Discuss the preventive effects of family-centered maternity care nursing on puerperal depression of delivery women during puerperal period and relieve burden of natural delivery women and decrease the possibility of delivery women's postpartum depression. Methods: 120 natural delivery women in the obstetrics of Yuhuangding Hospital from July 2015 to 2016 were randomly divided into two groups: the control group (n=60) was endowed with the conventional nursing. Delivery women accepted examination of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…This presentation of the data showed that FCCC is most effective in improving patient outcomes. [ 14 15 16 17 18 19 20 21 22 23 24 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 ] Several quotations supporting participants’ experiences were unclear because they were rarely accompanied by references to the source or context of the examples, and quotations were unclear whether they came from patients with psychosis, caregivers, or health system staff in this mixed-methods and qualitative study. [ 50 51 ]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This presentation of the data showed that FCCC is most effective in improving patient outcomes. [ 14 15 16 17 18 19 20 21 22 23 24 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 ] Several quotations supporting participants’ experiences were unclear because they were rarely accompanied by references to the source or context of the examples, and quotations were unclear whether they came from patients with psychosis, caregivers, or health system staff in this mixed-methods and qualitative study. [ 50 51 ]…”
Section: Resultsmentioning
confidence: 99%
“…Several RCTs were single blind; allocation concealment[ 14 35 ] or outcome assessor blinding[ 15 41 ] was done appropriately in these RCTs, although eight numbers of RCTs were double-checked blindly with allocation concealment and outcome assessor blinding[ 16 19 39 40 43 44 45 46 ] and the rest of them were not checked blindly. Besides, research designs were not mentioned in some studies,[ 23 24 35 39 40 49 ] while other studies did well with their research designs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations